Sensing the body matters: Profiles of interoceptive sensibility in chronic pain adjustment - Oliveira, I.; Garrido, M. V.; Carvalho, H.; Bernardes, S. F. (PAIN, 2024)
Interoception is critical to health regulation and is often disrupted in individuals with chronic pain (ICPs). Interoceptive sensibility (IS)—the self-reported experience and relationship toward internal states—includes skills such as sensing, interpreting, and using bodily information for self-regulation. Current studies on IS and chronic pain (CP) adjustment are scarce, and how the interplay between different IS skills shapes CP adjustment remains unclear. This cross-sectional study aimed to identify profiles of IS skills among ICPs and examined their associations with pain outcomes and psychological and behavioral risk or protective processes. Individuals with chronic musculoskeletal pain (n = 173; 84.4% women) completed the Multidimensional Assessment of Interoceptive Awareness (MAIA), measures of CP adjustment (depression, anxiety, vitality, pain severity, interference, and physical function), psychological (self-efficacy, catastrophizing, and kinesiophobia), and behavioral processes (activity patterns). A cluster analysis identified 3 IS skills profiles: (1) high IS skills (n = 68), with the highest levels of attention regulation toward bodily sensations, body trust, listening for insight, and self-regulation; (2) low IS skills (n = 29), who distracted less and worried more about bodily sensations, and presented lower-body trust; and (3) mixed IS skills (n = 71), despite good body trust, attention regulation, and low worrying, showed lower awareness of body–mind connections. Interoceptive sensibility skills profiles differed in depression, vitality (fatigue), and psychological or behavioral processes, such as pain-related self-efficacy, catastrophizing, kinesiophobia, and activity pacing. These findings contribute to integrating body–mind connections more explicitly into current theoretical CP models and developing tailored interventions targeting specific IS skills to improve CP adjustment.